Polarization rotation vector solitons in a graphene mode-locked fiber laser - Song, Yu Feng (2013)
Polarization rotation vector solitons formed in a fiber laser passively mode locked with atomic layer graphene were experimentally investigated. It was found that different from the case of the polarization locked vector soliton formed in the laser, two extra sets of spectral sidebands always appear on the soliton spectrum of the polarization rotating vector solitons. We confirm that the new sets of spectral sidebands have the same formation mechanism as that of the Kelly sidebands.